Effect of body position on prostate tumor hypoxia - Pyle, Joseph Gerard (Kansas State University, 2019)
Introduction: Arterioles of solid tumors lack innervation and functional smooth muscle, severely limiting vasomotor control and myogenic response. Previous research has shown that increasing mean arterial pressure via an exercise bout acutely improves prostate tumor perfusion and decreases tumor hypoxia. We hypothesized that increasing prostate tumor perfusion pressure using a hydrostatic gradient introduced by 70-degree head-up tilt could also increase tumor perfusion and decrease hypoxia, which could be clinically adapted to improve radiotherapy outcomes. Methods: 10⁴ Dunning R3327 AT-1 rat prostate adenocarcinoma cells were injected directly into the ventral lobe of the prostate of male Copenhagen rats (age 6 months, n=11). Six to eight weeks following injection, rats were given an intraperitoneal injection of hypoxic marker HypoxyprobeTM -1 and placed in either level (n=4) or 70-degree head-up tilt (n=7) condition. Tumors were removed and sectioned to be examined under microscope for HypoxyprobeTM -1 binding. Results: No significant difference was found in level of hypoxia between the level and 70-degree head-up tilt groups. Specifically, mean hypoxic cell count at supine was 1347 ± 271 and this did not change significantly in upright posture, which was 1410 ± 198 (P>0.05). Discussion: Contrary to our hypothesis we found no difference in tumor hypoxia between groups. This may be due to the age of the animals and the adoption of relatively healthy prostate arterioles during tumor development. Tumor vessels originate from vessels of healthy host tissue, which likely retain vasomotor and myogenic capability in young animals. The animals in this study were relatively young and likely restricted prostate blood flow and hence tumor blood flow in the head-up tilt condition. No immunocompetent aged rat prostate cancer model is currently available, future studies should focus on the development of this model, in order to accurately represent blood flow in host and tumor tissue.
Keywords: Kinesiology; Tumor Hypoxia